New evidence regarding the effects of contract farming on agricultural labor use - Anette Ruml; Matin Qaim (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2019)
Contract farming recently gained in importance in many developing countries. Various studies analyzed effects of contracting on productivity and income in the small farm sector. A few studies also looked at effects on agricultural labor use, suggesting that contracting tends to increase labor intensity, thus generating additional farm employment. An increase in the use of farm labor is plausible when contracting involves additional work in production, harvesting, and post-harvest handling. However, we argue that the opposite may also be true, namely when contracting involves labor-saving procedures and technologies. We use primary data from the oil palm sector in Ghana and show that farmers with a contract use significantly less labor per unit of land than farmers without a contract. We also analyze whose labor input is reduced. Household labor is reduced more than hired labor. Especially male household members reallocate time to off-farm employment. Contracts also reduce the likelihood of using child labor in farm production. This is the first study to show that contract farming reduces agricultural labor use in certain situations.
Keywords: J23; J43; O13; Q12; 330; contract farming; oil palm; agricultural labor use; rural employment; gender; child labor